Ten years of research on psychosocial risks, health, and performance in Latin America: A comprehensive systematic review and research agenda - Pujol-Cols, Lucas J. (2021)
Most systematic reviews of the relationships between work-related psychosocial risks, health, and performance have only considered papers in English, thus ignoring, to a considerable extent, studies conducted in Latin America. In addition, most systematic reviews that have indeed included Latin-American studies have focused on only one occupation and one kind of psychosocial risk, which contributes to producing scattered empirical evidence of this relationship. This paper reports the results of a comprehensive and critical systematic review of 85 studies that examined the relationships between psychosocial risks, health, and performance across a wide range of organizational contexts in Latin America over the last ten years. The paper contributes to the organizational psychology literature by critically reviewing and integrating the most recent studies on this topic in Latin America, identifying their main limitations, and proposing future lines of research that update the debate on this relationship and move this field of study forward.